RANBP2 is an allosteric activator of the conventional kinesin-1 motor protein, KIF5B, in a minimal cell-free system - Cho, Kyoung-in (Nature Publishing Group, 2009)
The association of cargoes to kinesins is thought to promote kinesin activation, yet the validation of such a model with native cargoes is lacking because none is known to activate kinesins directly in an in vitro system of purified components. The RAN-binding protein 2 (RANBP2), through its kinesin-binding domain (KBD), associates in vivo with kinesin-1, KIF5B/KIF5C. Here, we show that KBD and its flanking domains, RAN GTPase-binding domains 2 and 3 (RBD2/RBD3), activate the ATPase activity of KIF5B approximately 30-fold in the presence of microtubules and ATP. The activation kinetics of KIF5B by RANBP2 is biphasic and highly cooperative. Deletion of one of its RBDs lowers the activation of KIF5B threefold and abolishes cooperativity. Remarkably, RBD2–KBD–RBD3 induces unfolding and modest activation of KIF5B in the absence of microtubules. Hence, RANBP2 is the first native and positive allosteric activator known to jump-start and boost directly the activity of a kinesin.